Comparison of different time intervals between laparoscopic cholecystectomy to endoscopic retrograde cholangiopancreatography for patients with cholecystolithiasis complicated by choledocholithiasis - Hu, Lingbo; Shi, Xingpeng; Wang, Aidong (Frontiers in Surgery, 2023)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) followed by laparoscopic cholecystectomy (LC) is a common strategy for treatment of patients with gallstones with co-existing stones in the common bile duct (CBD). We conducted this study to compare the effect of different time intervals between ERCP and LC. Methods: A total of 214 patients who underwent elective LC after ERCP for gallstones and CBD stones between January 2015 and May 2021 were retrospectively reviewed. We compared the hospital stay, operation time, perioperative morbidity, and conversion rate to open cholecystectomy, according to the interval between ERCP and ERCP and LC, namely, one day, 2 to 3 days, and 4 days or more. A generalized linear model was used to analyze the differences among the groups for outcomes. Results: There were a total of 214 patients with 52, 80, and 82 patients in group 1, group 2, and group 3 respectively. These groups did not differ significantly in terms of major complications or conversion to open surgery (p=0.503 and p = 0.358, respectively). The generalized linear model showed that operation times in group 1 and group 2 were similar (odds ratio (OR) 0.144,95% confidence interval (CI) 12.597,8.511, p = 0.704), while operation time was significantly longer in group 3 than in group 1 (OR 4.005,95% CI 0.217,20.837, p = 0.045). Post-cholecystectomy hospital stay was similar among the three groups, while post-ERCP hospital stay was significantly longer in group 3 compared with group 1. Conclusion: We recommend that LC be performed within three days after ERCP to reduce operating time and hospital stay.